Optimizing rice (Oryza sativa L.) yield and lodging resistance using MGIDI and conventional selection indices - Durga Prasad Mullangie1,Kalaimagal Thiyagarajan1*,Manonmani Swaminathan2, Sritharan Natarajan2 and Senthilkumar Govindan2 (Electronic Journal of Plant Breeding)
To deal with the changing climate there is a necessity to develop climate resilient varieties without compromising yield. Hence concentrating on all the traits is essential to select genotypes. On utilization of the selection indices SI 1, SI 2, SI 3, and MGIDI we have observed that the modern selection indices such as MGIDI are superior over the Smith Index as MGIDI reported a gain of 2% in yield in F5 which simultaneously improved lodging resistance with a gain of 39.6% for section modulus and 34.7% for bending stress. In BC1F4, a selection gain of 5.80% for yield with simultaneous improvement in culm diameter at 5.89% gain was observed. Hence MGIDI was found to be superior over conventional indices, which improved both lodging resistance and yield.